2018
DOI: 10.3892/ol.2018.8901
|View full text |Cite
|
Sign up to set email alerts
|

Association between EGFR/KRAS mutation and expression of VEGFA, VEGFR and VEGFR2 in lung adenocarcinoma

Abstract: Epidermal growth factor receptor (EGFR) and Kirsten rat sarcoma viral oncogene homolog (KRAS) are two of the most notable driver genes in lung cancer, whilst vascular endothelial growth factor (VEGF) signaling serves a critical function in tumor angiogenesis. However, few studies have focused on the potential connection between EGFR/KRAS mutational status, and VEGFA, VEGF receptor (VEGFR)1 and VEGFR2 expression in lung adenocarcinoma. EGFR (exon 19, 20 and 21) and KRAS (exon 2) mutations were detected using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
(34 reference statements)
1
16
1
Order By: Relevance
“…Recently, some clinical trials (6, 9) of PD-1/PD-L1 inhibitors have demonstrated durable clinical benefit in many patients. Several studies reported that the expression of PD-L1 is closely related to EGFR (18) mutations, KRAS (19) mutations, smoking history (19) and advanced tumor stage (18, 20), but we failed to define a significant correlation between PD-L1 expression and these clinical features in LADC, which is concordant with the results of other studies (20, 21). In addition, some studies suggested that VEGFA expression has a significant association with EGFR mutations, advanced clinical stage and lymph node metastasis (21).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, some clinical trials (6, 9) of PD-1/PD-L1 inhibitors have demonstrated durable clinical benefit in many patients. Several studies reported that the expression of PD-L1 is closely related to EGFR (18) mutations, KRAS (19) mutations, smoking history (19) and advanced tumor stage (18, 20), but we failed to define a significant correlation between PD-L1 expression and these clinical features in LADC, which is concordant with the results of other studies (20, 21). In addition, some studies suggested that VEGFA expression has a significant association with EGFR mutations, advanced clinical stage and lymph node metastasis (21).…”
Section: Discussionsupporting
confidence: 90%
“…To date, there is little evidence on the role of KRAS status in D+R therapy (30). Although KRAS mutations might increase the expression of VEGF, VEGFR1 and VEGFR2 in various tumors including NSCLC, the underlying mechanisms is still unclear (31)(32)(33). In vitro data of ramucirumab showed inferior tumor regression in a KRAS mutated xenograft tumor (NCI-H2122) which could be significantly increased by the combination of ramucirumab with a pan-RAF inhibitor (34).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is proposed as a mechanism of resistance to anti-EGFR therapies that could be reversed [ 122 , 123 , 124 , 125 , 126 ]. For example, Yuan et al explored associations between angiogenesis-inducible factor expressions and the presence of EGFR and KRAS (Kirsten ras oncogene homolog) mutations to specify the relationship between oncogenic alterations and hypoxia [ 127 ]. EGFR mutations concerning 21 or 20 exons ( p = 0.002) were associated with significantly high levels of VEGF-A.…”
Section: Biological Features Associated With Hypoxia In Nsclcmentioning
confidence: 99%